Minds make societies: how cognition explains the world humans create - Boyer, Pascal (Yale University Press, 2020)
Preface -- Introduction: Human societies through the lens of Nature -- Six problems in search of a new science -- 1. What is the root of group conflict? Why "tribalism" is not an urge but a computation -- 2. What is information for? Sound minds, odd beliefs, and the madness of crowds -- 3. Why are there religions? ... And why are they such a recent thing? -- 4. What is the natural family? From sex to kinship to dominance -- 5. How can societies be just? How cooperative minds create fairness and trade, and the apparent conflict between them -- 6. Can human minds understand societies? Coordination, folk sociology and natural politics -- Conclusion: Cognition and communication create traditions.